New Records of Helminth Parasites in Amphibians from the South American Chaco - González, Marisa Analia (2025)
This study aims to identify the helminth fauna of anurans from Argentina´s Dry and Humid Chaco ecoregions. We examined 152 specimens of 12 anuran species belonging to the families Hylidae, Leptodactylidae, and Microhylidae from 3 areas located in the provinces of Chaco and Formosa (Dry Chaco) and in Corrientes province (Humid Chaco). A total of 17 helminth taxa were found: acanthocephalans in the larval stage (Centrorhy-nchus sp.), nematodes in the larval stage (Contracaecum sp., Porrocaecum sp., Physaloptera sp., aff. Cystidicolidae), and nematodes in the adult stage (Rhabdias sp., R. elegans, Strongyloides pereirai, Oswaldocruziaproencai, O. subauricularis, Parapharyngodon senisfaciecaudus cubensis, Aplectanahylambatis, Cosmocercaparva, C. podicipinus, Cosmocercella phyllomedusae, Schrankiana formosu-la, Falcaustra mascula). This study presents new host and geographic records and expands knowl-edge of helminth diversity in a critically threatened group of vertebrates.